Forced Convection Heat Rejection System for Mars Surface Applications - Colgan, Nathan; Nellis, Gregory; Anderson, Mark (Proceedings of the Wisconsin Space Conference, 2022)
A forced convection heat exchanger for waste heat rejection to the Martian atmosphere is designed based on existing heat transfer and pressure drop correlations for low-Reynolds-number finned tube arrays. The design is optimized to determine the mass-optimal heat exchanger geometry for a range of candidate heat exchanger materials and power loads. For a 100 kW thermal load, the optimal heat exchanger mass is found to be 27.0 kg and a frontal area of 3.94 m2. This is 95% less mass and area than a comparable radiator and only requires 638 W of fan power (or 0.6% of the output power) to operate. Optimal geometries are also found for heat rejection loads of 1 kW to 250kW across a range of coolant and atmosphere temperatures, indicating wide applicability of this technology for Martian heat rejection applications such as cryofuel refrigeration or in-situ resource utilization (ISRU) plant cooling. An experimental facility has been designed and partially constructed to experimentally validate the predicted heat exchanger performance in a Mars-like environment. A subscale heat exchanger has been built based on the predicted mass-optimal geometry. Heat transfer and pressure drop performance data of this heat exchanger will be collected and will refine the modelling predictions.